EMOTIONAL INTELLIGENCE DIFFERENCES BETWEEN THE FOLLOWING STUDENTS EXTRACURRICULAR FOOTBALL AND NOT FOLLOWING IN SMPN 10 BEKASI - Yusuf, Andri Hermawan (2013)
The purpose of this study was to reveal differences in emotional intelligence of students who take extracurricular football and not follow in SMPN 10 Bekasi. The method used in this study was ex post facto with the sample of 30 students who take extracurricular football and 30 students who did not attend extracurricular SMPN 10 Bekasi. Data collection instrument in this study is the use of a closed questionnaire. The hypothesis of this study is that there is no significant difference in the emotional intelligence of students who take extracurricular football and who does not follow in SMPN 10 Bekasi. After the calculation technique with independent sample t test obtained = 5,522 and t table = 2:00. because the value of t count> t table (5,522> 2.00) and significant (0.000 <0.05), then Ho is rejected, it means that there is a difference between the average value of emotional intelligence among the students who take the students' extracurricular football and did not follow . The average (mean) for the following extracurricular football is 146.57 and for which no follow is 134.50, meaning that the average value of emotional intelligence that follows football extracurricular higher than the average value of emotional intelligence are not following extracurricular. While the average difference (mean diference) of 12,067 (146.57 -134.50) and the difference ranged between 7,692 to 16,450. Keywords: Emotional Intelligence, Students, ExtracurricularFootball.